2018
DOI: 10.1021/acs.analchem.8b03083
|View full text |Cite
|
Sign up to set email alerts
|

Universal Ti3C2 MXenes Based Self-Standard Ratiometric Fluorescence Resonance Energy Transfer Platform for Highly Sensitive Detection of Exosomes

Abstract: Exosomes, as novel noninvasive biomarkers for disease prediction and diagnosis, have shown fascinating prospects in monitoring cancer-linked public health issues. Herein, a unique Cy3 labeled CD63 aptamer (Cy3-CD63 aptamer)/Ti 3 C 2 MXenes nanocomplex was constructed as a self-standard ratiometric fluorescence resonance energy transfer (FRET) nanoprobe for quantitative detection of exosomes. The Cy3-CD63 aptamer can be selectively adsorbed onto the Ti 3 C 2 MXene nanosheets by hydrogen bond and metal chelate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(173 citation statements)
references
References 45 publications
3
164
1
Order By: Relevance
“…In the case of ssDNA labeled by FAM, the uorophore interacted mainly with the surface, whereas in the case of dsDNA the FAM not only interacted with the surface but also with the end of the double helix by stacking. These observations can explain the quenched uorescence of ssDNA which has also been evidenced in recent works, 37,58 and can be assigned to resonant electron transfer given the spectral overlap and the low-range distance. But given the low distance (#10Å), the question of whether Dexter energy transfer has a role also arises.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In the case of ssDNA labeled by FAM, the uorophore interacted mainly with the surface, whereas in the case of dsDNA the FAM not only interacted with the surface but also with the end of the double helix by stacking. These observations can explain the quenched uorescence of ssDNA which has also been evidenced in recent works, 37,58 and can be assigned to resonant electron transfer given the spectral overlap and the low-range distance. But given the low distance (#10Å), the question of whether Dexter energy transfer has a role also arises.…”
Section: Resultssupporting
confidence: 78%
“…[32][33][34][35] Very recently, a nanopore DNA sequencing system has been reported with MXene membranes. 36 Aptamer-based assays have also been recently developed for exosome detection, 37,38 as well as MXene composites with DNA for dopamine detection. 39 Herein, we probe the interaction between single-and double-stranded DNA with Ti 3 C 2 T x , the most studied and widely used MXene, by means of uorescence spectroscopy and molecular dynamics (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the quenched fluorescent signal linearly correlated to the concentration range of 1.0 × 10 4 -1.0 × 10 8 EVs/µL and reached a LOD of down to 1.1 × 10 3 EVs/µL. Lee et al developed a selective and sensitive system to detect exosomal miRNA ( Figure 2D) by using the quenching and recovery of fluorescence mechanism, as well as the metal-enhanced fluorescence of a multifunctional single nanorod structure with magnetic and plasmonic components [63]. Each component was specifically modified to selectively isolate targeted EVs through magnetic immunoseparation and sensitively and selectively identify targeted exosomal miRNA using a fluorophore-labeled hairpin single-stranded molecular beacon.…”
Section: Colorimetric/fluorescence-based Analysis Methods For Ev Detementioning
confidence: 99%
“…The biosensor exhibited an excellent performance by analysis of spiked serum samples with recovery indices from 95 % to 104 % . In the next study from the same group, it was shown that, besides CD63 and EpCAM, other proteins present on the surface of the exosome can be targeted by DNA aptamers, including PSMA and PTK‐7 . Another MXene‐based biosensor for the detection of exosomes was studied by Fang et al .…”
Section: Electrochemical Exosome Biosensingmentioning
confidence: 96%